2016
DOI: 10.14800/ccm.1216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neonicotinoids on Promoter-Specific Expression and Activity of Aromatase: Implications for the Development of Hormone-Dependent Breast Cancer

Abstract: Aromatase (CYP19) is the key enzyme in the biosynthesis of estrogens. In humans, it is expressed in a tissue-and promoter-specific manner. In hormone-dependent breast cancer, CYP19 is overexpressed through the activation of several additional promoters (PII, I.3 and I.7) that are normally inactive in the healthy mammary gland. In the normal mammary gland, low basal CYP19 expression is regulated by the I.4 promoter, which is also active in adipose tissue. Here, we highlight our recent study of the effects of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…A previous study from our institute used publicly available data and identified 296 chemicals that increased E2 (182), P4 (185) or both (71) from 2,012 chemicals tested in the HT-H295R assay as part of US EPA’s Tox21/ToxCast program 5 . This assay is internationally validated for regulatory contexts by the Organization for Economic Co-operation and Development (OECD) 11 , 12 and slight variations are also used for research purposes 13 18 . We have shown that chemicals known to cause mammary gland effects in vivo are enriched for increasing E2 and P4 steroidogenesis 5 , so exposure to these chemicals may also increase breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study from our institute used publicly available data and identified 296 chemicals that increased E2 (182), P4 (185) or both (71) from 2,012 chemicals tested in the HT-H295R assay as part of US EPA’s Tox21/ToxCast program 5 . This assay is internationally validated for regulatory contexts by the Organization for Economic Co-operation and Development (OECD) 11 , 12 and slight variations are also used for research purposes 13 18 . We have shown that chemicals known to cause mammary gland effects in vivo are enriched for increasing E2 and P4 steroidogenesis 5 , so exposure to these chemicals may also increase breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%